2011
DOI: 10.1539/joh.10-0072-oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatigue on Immune Function in Nurses Performing Shift Work

Abstract: Effects of Fatigue on Immune Function in Nurses PerformingShift Work: Makie Nagai, et al. Department of Epidemiology and Public Health, Kanazawa Medical University-Objectives:We investigated the effects of fatigue on NK cell function and lymphocyte subpopulations in nurses performing shift work using a longitudinal design. Methods: Fiftyseven female nurses engaged in shift work at a hospital in Japan were selected for our study cohort. The hospital used a counterclockwise rotating three-shift system. Night shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 24 publications
4
38
1
4
Order By: Relevance
“…lymphocytes and NK cells activity) and mental (e.g. oxidative stress, anxiety) systems (Froy, 2010;Guo et al, 2013;Ö zdemir et al, 2013;Nagai et al, 2011;Selvi et al, 2010). Also, peripheral clock gene expression was shown to be disturbed (Bracci et al, 2014;Takahashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…lymphocytes and NK cells activity) and mental (e.g. oxidative stress, anxiety) systems (Froy, 2010;Guo et al, 2013;Ö zdemir et al, 2013;Nagai et al, 2011;Selvi et al, 2010). Also, peripheral clock gene expression was shown to be disturbed (Bracci et al, 2014;Takahashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The observed changes in shift work, such as continuous sleep deprivation, stress and a change of the natural circadian pattern can also influence the immune response among individuals [63], [64], [65]. However, there is a scarcity of studies on the subject with even more conflicting results [66], [67] and perhaps their heterogeneity, using different populations and samples and types of shift work evaluated, makes such conclusions difficult (Table 2).…”
Section: Sleep and Immunitymentioning
confidence: 99%
“…Nagai et al [65] demonstrated that shift work is also associated with depression of the innate immune response, exhibiting a decrease in NK cell activity associated with an increase in fatigue compared to day workers (p<0.001). However, in two other studies conducted at the same time [66], [67], different results were observed.…”
Section: Sleep and Immunitymentioning
confidence: 99%
“…In addition, circadian disruption has profound effects on the immune system, which has been evidenced both in animal models and in human studies. Female nurses working in a three-shift rotating system showed a progressive decrease in natural killer (NK) cell activity and CD16 + CD56 + cells number (Nagai et al 2011). Shift working has also been linked to a higher risk for common infections, with the highest risk in workers going through three different shifts (Mohren et al 2002).…”
Section: Immune Alterationsmentioning
confidence: 99%